IMPLEMENTASI METODE MIND MAPPING PADA PEMBELAJARAN PENDIDIKAN TARIKH DI SMA MUHAMMADIYAH 5 YOGYAKARTA - Nurudin, M Fatwa; Makrufi, Anisa Dwi (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang (UIN) Raden Fatah Palembang, 2023)
The purpose of this study is to determine the effectiveness of the implementation of the mind mapping method in learning Tarikh Education. This type of research is class action research that is applied to the subject of Date Education for class X students of SMA Muhammadiyah 5 Yogyakarta. Data collection techniques are carried out by observation, interview, and documentation methods. Meanwhile, data analysis is carried out through three stages of activities that occur simultaneously, namely: data reduction, data presentation and drawing conclusions / verification. The results of the study showed that the implementation of the mind mapping method in the learning of Tarikh Education at SMA Muhammadiyah 5 Yogyakarta had a positive impact on students and teachers. Judging from the increase in shiva's understanding and enthusiasm in participating in learning. The conclusion of this study is that the mind mapping method is effective to be implemented in the learning of Tarikh Education at SMA Muhammadiyah 5 Yogyakarta.